An empirical assessment of which inland floods can be managed. (1st February 2016) - Mogollón, Beatriz; Frimpong, Emmanuel A.; Hoegh, Andrew B.; Angermeier, Paul L.
Abstract: Riverine flooding is a significant global issue. Although it is well documented that the influence of landscape structure on floods decreases as flood size increases, studies that define a threshold flood-return period, above which landscape features such as topography, land cover and impoundments can curtail floods, are lacking. Further, the relative influences of natural versus built features on floods is poorly understood. Assumptions about the types of floods that can be managed have considerable implications for the cost-effectiveness of decisions to invest in transforming land cover (e.g., reforestation) and in constructing structures (e.g., storm-water ponds) to control floods. This study defines parameters of floods for which changes in landscape structure can have an impact. We compare nine flood-return periods across 31 watersheds with widely varying topography and land cover in the southeastern United States, using long-term hydrologic records (≥20 years). We also assess the effects of built flow-regulating features (best management practices and artificial water bodies) on selected flood metrics across urban watersheds. We show that landscape features affect magnitude and duration of only those floods with return periods ≤10 years, which suggests that larger floods cannot be managed effectively by manipulating landscape structure. Overall, urban watersheds exhibited larger (270 m 3 /s) but quicker (0.41 days) floods than non-urban watersheds (50 m 3 /s and 1.5 days). However, urban watersheds with more flow-regulating features had lower flood magnitudes (154 m 3 /s), but similar flood durations (0.55 days), compared to urban watersheds with fewer flow-regulating features (360 m 3 /s and 0.23 days). Our analysis provides insight into the magnitude, duration and count of floods that can be curtailed by landscape structure and its management. Our findings are relevant to other areas with similar climate, topography, and land use, and can help ensure that investments in flood management are made wisely after considering the limitations of landscape features to regulate floods. Highlights: Floods with return periods ≤10 years can be managed by manipulating the natural or built environment. Built flow-regulating features lower flood magnitude but do not lengthen flood duration. Forested watersheds regulate small floods more effectively than watersheds with flow-regulating features.